A review on carbon membranes for hydrogen purification - Norazlianie, Sazali; M. F., Ghazali; J. P., Siregar; T., Gunawan; W. N. W., Salleh; N., Yusof (IOP Publishing, 2020)
Hydrogen (H2) as a high competence and clean energy bearer has pulled in reestablished and consistently expanding consideration around the globe as of late, basically because of advancements in power modules and ecological weights including environmental change issues. In thermochemical forms for H2 creation from non-renewable energy sources, separation and purification performance is a basic innovation. Specifically, microporous membranes indicate guarantees in water gas move response at higher temperatures. In this article, we survey the look at the basic issues in these membranes as for the specialized and financial focal points and weaknesses. Conclusions will be made on the significance of membrane innovation to the new age of zero-outflow control advancements.